2016
DOI: 10.1111/1471-0528.14019
|View full text |Cite
|
Sign up to set email alerts
|

Labour patterns in Chinese women in Chongqing

Abstract: Population The final sample involved 1200 Chinese parturients with singleton, vertex and term gestation; spontaneous onset of labour; vaginal delivery; and without adverse perinatal outcomes.Methods A repeated-measures analysis was used to depict labour curves while an interval-censored regression was used to estimate the duration of labour centimetre by centimetre.Main outcome measures Labour curves and the duration of labour at the 50th and 95th percentiles.Results Among 1091 nulliparous women, 57.7% had cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 17 publications
7
32
1
Order By: Relevance
“…Zhang et al 2 found that there was no significant deceleration phase in labor. No deceleration phase was observed in a study by Suzuki et al 11 regarding labor of Japanese primipara and in a study by Shi et al 3 regarding labor of Chinese primiparas. In our study, we did not find any deceleration phase in labor of parturients with VBCA ( Figure 1).…”
Section: Deceleration Phasementioning
confidence: 78%
“…Zhang et al 2 found that there was no significant deceleration phase in labor. No deceleration phase was observed in a study by Suzuki et al 11 regarding labor of Japanese primipara and in a study by Shi et al 3 regarding labor of Chinese primiparas. In our study, we did not find any deceleration phase in labor of parturients with VBCA ( Figure 1).…”
Section: Deceleration Phasementioning
confidence: 78%
“…when the median dilatation rate became 1.09 cm/hour) (OT Oladapo et al., unpubl. data) 6, 7, 21, 22, 24. The transition to more rapid progress started between 5 and 6 cm, but it was only after 6 cm that the dilatation rate doubled (Figure S2).…”
Section: Resultsmentioning
confidence: 96%
“…Of the seven studies examining nulliparous women, four were considered to be at low risk of bias (OT Oladapo et al., unpubl. data),6, 21, 22 two at moderate risk of bias,7, 24 and one at high risk of bias 23. All three studies examining parous women were assessed to be at low risk of bias (OT Oladapo et al., unpubl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations